Pandemic and the Mongoloid Phenotypes in India - Chanu, Naorem Pushparani; Chakraborty, Gorky (Social Change, 2024)
Epidemics are biological processes that appear suddenly as shocks. Societies attempt to negotiate such shocks through the interplay of classes, ethnicities, and institutions. In the process, does it create newer fault lines or consolidate the pre-existing
Keywords: Mongoloid Phenotype; Out-Migration; Pandemic; Racial Discrimination; Northeast India